Faktor – Faktor Yang Berhubungan Dengan Imunisasi Dasar Lengkap: Factors Associated with Complete Basic Immunization - Astuti, Haryati (Jurnal Kebidanan Midwiferia, 2017)
The five basic immunizations consist of HB0 first time, 1 time BCG , 4 times Polio, 3 times DPT-HB-Hib, 1 time Measles. In Indragiri Hilir district, vaccination coverage was 55.7% in 2015, and in Tembilahan Hulu health center was 88%, that has not reached the target of 100%. The objective of reasearch is to detect the proportion of babies who are not received basic immunization and the factors associated with the complete basic immunization in Tembilahan Hulu Health Center. Method: The design type of research is analytic cross-sectional. Population is 802 babies < 2 years. Based on the type of research design, significant level of 5%, strength of test of 90%, the sample size is 220 r babies < 2 year. This samples were taken from the population by using systematic random sampling. The collection of primary data through structured interviews with closed ended questions. Data were analyzed by univariate, bivariate and multivariate logistic regression analysis.Research of result: The babies who are not given basic immunizations were 51.8% in the sample, and 45.2% -58.4% in population.. There are causal relationship between each of independent variables namely neonatal visit (C.I 95%: 2.200 to 7.343), and birth attendants (C.I 95%: 1.192 to 6.736). with complete basic immunization: Recommendation: The babies should have completet basic immunization , when health workers from health center do neonatal visit in the period of 0-7 days after birth, and the mother giving birth help by skilled health personnel. Based on the recommendation, suggestion formulated.